2012
DOI: 10.1177/1934578x1200700737
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oil of Heracleum rigens

Abstract: The essential oil was extracted from the seeds of Heracleum rigens by hydrodistillation and a total of twenty compounds accounting for 98.5% of the total oil composition were identified. Physicochemical properties and chemical composition of the oil was determined by a combination GC/FID and GC/MS analysis. The major compounds identified were bornyl acetate (51.2%), α-pinene (22.6%), limonene (9.62%), octyl acetate (3.94%), p-cymene (2.85%) and γ-terpinene (1.93%). The antimicrobial activity of the oil was scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Another ester, n-octyl acetate, was reported as a common component in most fruit oils of Heracleum genus [12]. Bornyl acetate (51.20%) was the major compound in the essential oil of Heracleum rigens seeds [13]. The differences between our study and others could be explained by the fact that we investigated the whole aerial parts of the plant.…”
contrasting
confidence: 60%
“…Another ester, n-octyl acetate, was reported as a common component in most fruit oils of Heracleum genus [12]. Bornyl acetate (51.20%) was the major compound in the essential oil of Heracleum rigens seeds [13]. The differences between our study and others could be explained by the fact that we investigated the whole aerial parts of the plant.…”
contrasting
confidence: 60%
“…However, there is no particular data suggesting synergism between bornyl acetate and other terpenes. Some studies have demonstrated synergism mainly produced between oxygenated terpenes (Sokovic et al 2010;Fidan et al 2019;Bassole and Juliani 2012;Novato et al 2019;Gavaric et al 2015;Jagannath et al 2012). Thus, in further studies, synergism of bornyl acetate with other terpenes should be investigated.…”
Section: Discussionmentioning
confidence: 95%
“…The described approach focused on major compounds found in CEOs since full-deck quantification of all terpenes is not feasible due to lack of reference material and detection limits. Based on the previous analysis of the chemical composition of CEOs and the knowledge of their possible antibacterial properties, eight terpenes are chosen for this study (Jagannath et al 2012). The relative amounts of the selected terpenes in the analyzed CEOs are presented in Supplementary Table 7S.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the essential oils showed weak antibacterial property against Gram‐positive bacterial strains of S. aureus and Staphylococcus epidermis with no measurable effect on E. coli and P. aeruginosa (Torbati and others ). Jagannath and others () tested the antimicrobial effects of H. rigens against 9 pathogenic bacteria. Maximum activity was noted for Klebsiella pneumonia and B. subtilis .…”
Section: Biological Activitiesmentioning
confidence: 99%